2004
DOI: 10.1111/j.0967-0750.2004.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of interregional mobility in Russia

Abstract: The paper studies the determinants of internal migration in Russia. Using panel data on gross region-to-region migration flows in 1992-99, we estimate the effect of economic, political and social factors. Although overall migration is rather low, it turns out that its intensity does depend on economic factors even controlling for fixed effects for each origin-destination pair. People move from poorer and job scarce regions with worse public good provision to those which are richer and prospering better both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
209
3
17

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(235 citation statements)
references
References 25 publications
6
209
3
17
Order By: Relevance
“…3 See also McKenzie and Rapoport's 2010 analysis of migration networks' role in migrant selection with respect to education. for Brazil; Chernina et al, 2013, for the late Russian Empire, and Andrienko andGuriev, 2004, Guriev andVakulenko, 2013, for post-Soviet Russia). On the other hand, a recent paper by Beegle et al (2011) finds no evidence that household wealth restricts migration in Tanzania, whereas Abramitzky et al (2012) find a negative relationship between wealth and the probability of both internal and international migration in the analysis of historical mass migration from Norway to the US.…”
Section: Introductionmentioning
confidence: 99%
“…3 See also McKenzie and Rapoport's 2010 analysis of migration networks' role in migrant selection with respect to education. for Brazil; Chernina et al, 2013, for the late Russian Empire, and Andrienko andGuriev, 2004, Guriev andVakulenko, 2013, for post-Soviet Russia). On the other hand, a recent paper by Beegle et al (2011) finds no evidence that household wealth restricts migration in Tanzania, whereas Abramitzky et al (2012) find a negative relationship between wealth and the probability of both internal and international migration in the analysis of historical mass migration from Norway to the US.…”
Section: Introductionmentioning
confidence: 99%
“…These might be thought of as non-core variables and constitute, together with the core variables, an extended H-T model. Such extended H-T models have been recently successfully applied to regional migration in countries such as Russia (Andrienko and Guriev 2004) and Poland (Ghatak et al 2008), where in both cases the core and a range of non-core variables were found to be significant.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, an important distinction. The pattern of decline of NMR reflects important regional differences (see Figure II) notably the decling relative attractiveness of regions such as Siberia (Andrienko and Guriev 2003). These patterns have changed somewhat after the year 2000.…”
Section: A An Examination Of the Datamentioning
confidence: 95%
“…Empirical evidence (Andrienko and Guriev 2003) seems to suggest that migration rates are not in fact high, and can be largely explained by traditional factors, although there has been some change of regional migration patterns in the past few years. Nevertheless, the subject has attracted considerable attention (Gerber 2000, Heleniak 2002).…”
mentioning
confidence: 99%